Analysis of the Factor of Safety (FS) in Slope Stability Against Blasting Activities at Pit X, South Kalimantan - Sahya, Muhammad Mufty Zaki; Misbahuddin (UIR PRESS, 2024)
Blasting is used to break hard rock in mining, but the vibrations can destabilize the slope through the resulting soil vibrations. The resulting blasting vibration must be in a safe condition, especially the stability of the mine slope around the blasting. This study aims to analyze the value of the slope factor of safety (FS), blasting soil vibration, and the influence of soil vibration on the value of the factor of safety (FS). The research method involves data collection followed by slope stability analysis utilizing the Bishop Simplified Method within Slide software and blasting vibration analysis using regression models to determine Maximum Horizontal Acceleration (Amax). The study results showed that the value of FS varied based on location and geological conditions. The A-A' section in the upper western part of the mine has the highest FS value of 2.36, while the C-C' cross-section in the lower eastern part of the mine has the lowest FS value of 1.16. Analysis of soil tremors in Amax values showed the highest values in August and the lowest at the end of October. The Amax value has an effect on the decrease in the FS value based on the blasting distance. The B-B' cross-section has the largest influence, the A-A' and C-C' cross-sections have a fairly small influence, and the D-D' cross-section has no influence.